2016
DOI: 10.1016/j.tranpol.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Economic savings linked to future Arctic shipping trade are at odds with climate change mitigation

Abstract: This paper assesses costs, emissions, and climate impact by freight shipping in the Arctic with main focus on the Northern Sea Route. The entire route lies in Arctic waters, which due to global warming, has become ice free during summer and autumn. The route goes from the Atlantic Ocean to the Pacific Ocean along the Russian Arctic coast and reduces voyage distance by 40 % between Northern Europe and Japan. Traditionally, comparisons of the climate impact of transport solutions have been based on fuel consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 39 publications
(35 reference statements)
0
37
0
Order By: Relevance
“…Guy (2006) found that the NWP is cost-competitive under specific scenarios whilst Faury and Cariou (2016) found the NSR to be cost-competitive in specific months of the year. Of the eight studies that appraised emissions, one concluded that Arctic routes are less energy efficient than the traditional ones (Lindstad et al, 2016).…”
Section: Cost Operational and Revenue Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Guy (2006) found that the NWP is cost-competitive under specific scenarios whilst Faury and Cariou (2016) found the NSR to be cost-competitive in specific months of the year. Of the eight studies that appraised emissions, one concluded that Arctic routes are less energy efficient than the traditional ones (Lindstad et al, 2016).…”
Section: Cost Operational and Revenue Factorsmentioning
confidence: 99%
“…Wang et al (2016) argued that if the time value of cargo is included in Lasserre's (2014) calculations, then both the NSR and NWP are more competitive than the Suez route by 3% and 65% respectively on the Rotterdam-Shanghai route and 52% and 85% on the Rotterdam-Yokohama route respectively. The Arctic routes are shown to be competitive in almost all of the papers considering single/round voyages as well as in Lindstad et al (2016), who did not explicitly define the time frame. The competitiveness of the NSR ranges from 0.5% (Schøyen and Bråthen, 2011) to 47.…”
Section: Cost Operational and Revenue Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some landscape events, such as the opening up of a route in the Arctic, can be expected to stimulate further trade (Smith and Stephenson, 2013;Lindstad et al, 2016), as can deliberate attempts to increase commodity flows (Clott et al, 2015). Such comments apply to short-sea shipping equally (Morales-Fusco et al, 2012;.…”
Section: Discussionmentioning
confidence: 99%
“…Potential environmental benefits would include fewer emissions, reduced fuel requirements, and less time spent travelling between locations. Although these new shipping routes provide immense economic benefits to the shipping industry, there are numerous potentially adverse environmental consequences to their use (Lindstad et al 2016). Atmospheric and marine pollution are likely to increase in Arctic regions, as will the risk of bioinvasions due to the spread of invasive species released via ballast water (Seebens et al 2013).…”
Section: Roads As Fragmenting Featuresmentioning
confidence: 99%